New Zealand views, 1880-1889. - Burton Brothers (1880)
Album includes views of Auckland, Napier, Mount Turawera, Waikato River, Wellington, Maori houses, Christchurch, Dunedin and Milford Sound.
Title devised by cataloguer.
Condition: Yellowing and spotting.
Keywords: Public buildings -- New Zealand -- Photographs; Dwellings -- New Zealand -- Photographs; Mountains -- New Zealand -- Photographs; Bays -- New Zealand -- Photographs; New Zealand -- Buildings, structures, etc. -- Photographs; New Zealand -- Photographs